Detecting Appropriate Solution to Elementary School Students’ Mathematic Learning Problem - Dinda Maemunah; Cecep Kustandi; Iva Sarifah (Jurnal Elementaria Edukasia, 2024)
Mathematics is used in various fields of social life, in the economic field it is used for buying and selling, in architecture it is used to calculate and measure so that estimates are accurate, in the field of art as a tool for calculating patterns, movements, sketches, etc. Direct experience is considered direct participation in activities that can give rise to initial reactions, visual impressions and emotional responses. Students are encouraged to acquire new real-world skills and competencies by gaining knowledge of common roles in a variety of situations, locations, and environments. This experiential learning model provides students with different learning situations in the form of participation in direct experiences designed by the teacher. This research is the initial stage of development research (R&D), therefore the research carried out is limited to needs analysis (need assessment). This research uses qualitative descriptive research conducted with a case study approach which is based on human understanding and behavior based on human opinion. This research aims to collect information regarding the needs of fifth grade elementary school students in spatial building materials. This research is qualitative descriptive research with a case study approach. Data collection was carried out by interviews and distributing questionnaires via Google Forms which were distributed to 30 class VI students as respondents. The results of the research show that class V students need innovation to implement a learning model that is more effective and can provide students with learning experiences, namely the experiential learning model.